PERAN GENDER DALAM PEKERJAAN - Dama Putri, Syahqi Nadiva; Setyowati, Niken Ayu; Khaerunnisa, Handini Putri; Hadiwana, Venencia Elvara Putri; Listyani, Refti Handini (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
The employment of female workers (TKW) has become a significant social phenomenon in the context of globalization and migration. In this study, we focus our attention on the role of gender in the work of migrant workers, using the Karawang case study as a background. The aim of this research is to assess, analyze and understand how gender roles influence the work of TKW in Karawang, as well as its impact on their welfare. This research was conducted using a qualitative approach. Research findings show that gender roles in TKW work in Karawang are closely related to cultural norms, community expectations and job demands. The work carried out by migrant workers is often influenced by gender stereotypes which lead to job segregation based on gender. We also found that gender roles influence income levels, access to certain jobs, and understanding of their rights as migrant workers. The impact of these gender roles not only includes economic aspects, but also physical and emotional aspects of migrant workers' well-being.